Human Resource Development Strategies of the Social Affairs Office in Handling Abandoned Children in Minahasa Regency - Maya C. Rambitan; Deitje A. Katuuk; Jeffry Sony Junus Lengkong; Mozes M. Wullur; Ruth Umbase (JR Education, 2026)
Abandoned children represent a persistent social problem with long-term implications for educational attainment, psychosocial wellbeing, and the quality of future human resources. This article reformulates a doctoral dissertation into a journal-style paper and examines how the Social Affairs Office of Minahasa Regency designs, implements, and evaluates human resource development strategies for abandoned children from an educational management perspective. The study employed a qualitative descriptive design. Data were generated through in-depth interviews, field observations, and document analysis, then analyzed using the interactive model of Miles and Huberman through data reduction, data display, and conclusion drawing. The findings indicate that the strategy has been organized through planning, organizing, actuating, and controlling (POAC), supported by legal mandates and cross-sector coordination with police, women and child protection agencies, local communities, and child welfare institutions. In practice, however, the strategy shows uneven effectiveness. It is relatively strong in basic-needs fulfillment, emergency response, administrative verification, and short-course skills training, but remains weaker in formal education reintegration, sustained psychosocial recovery, family reunification quality, and long-term social integration. Key enabling factors include regulatory support, institutional collaboration, and the existence of non-formal training initiatives, while key barriers include inadequate budget allocation, insufficient qualified social workers, limited facilities, weak outcome-based evaluation, low public participation, and low motivation among many children to re-enter school. The article argues that abandoned children's development should not be treated merely as a welfare intervention but as a long-horizon educational management process. Based on the findings, a strengthened educational management strategy is proposed, integrating measurable educational indicators, competency development for social workers, stronger community participation, digitalized case management, and continuous CIPP-based evaluation. Such a strategy is necessary to transform short-term rescue efforts into sustainable human resource development outcomes.